Automated WEC Metocean design basis from ResourceCode data. (Proceedings of the European Wave and Tidal Energy Conference, 2025)
In recent years, the development of wave energy converters (WEC) entered a phase of renewal,as pointed by the Ocean Energy Europe “Wave energy development highlight 2023”. The R&D support for wave energy made substantial progress during the last decade, and one of the flagship projects of this global effort was Resourcecode. This project aimed at providing Europeandevelopers with high quality MetOcean data, free to use, for a large portion of the European Atlantic and North Sea waters on a fine grid. During the same period, the IEC TS 62600 group kept on  advancing and publishing new technical specifications for the development of WECs, and now a corpus of reference documents is available to the wave energy stakeholders, guiding their technicalactivities, and ensuring the sound development of the technologies and projects. Among those, the IEC TS 62600-2 and IEC TS 62600-10 specifies the design requirements for marine energy converters, and the IEC TS 62600-101 guides the wave energy converters resource assessment. These requirements specify the dynamic load cases and associated MetOcean conditions that engineers must consider during the design of a WEC.The work presented here was conducted within the WEDUSEA project, which aims at deployment of prototype OE35 at EMEC. The feedback on IEC 62600 technical specifications is an important secondary objective. During the design phase, the need to define a MetOcean design basis led to the development of an automated tool to use the Resourcecode database to extract the relevant data. The article reports on this automated tool and the validity of the results with regards to the IEC 62600 requirements. By correlating the definition of the Resourcecode under lying Metocean models and inputs, it is established that, in most cases, the use of the Resourcecode data could beused to satisfy the Class I: Reconnaissance and Class II: Feasibility levels of wave resource assessment defined in IEC TS 62600-101. The Resourcecode database is however not sufficient to provide the necessary level of information for the wind, current, water level and secondary environ-mental conditions.The automated tool itself introduces new plots and graphic derived from the Resourcecode database that are derivedto support WEC design specifically. Examples of the resultsobtained for the WEDUSEA planned deployment location are provided. Such elements are the evolution of key parameters such as mean wave direction of propagation.